Optical Coherence Tomography Significance in Managing Early Onset of Optic Pathway Gliomas in Children Younger than 5 Years of Age-A Retrospective Study - Rossana Pavone; Carla Fonte; Iacopo Sardi; Roberto Caputo; Elisa Marziali; Fabio Mazzeo; Jacopo Secci; Alessia Bergamini; Salvatore De Masi; Maria Carmela Leo; Maria Luigia Censullo; Giacomo Maria Bacci (MDPI AG, 2022)
We aimed to investigate the significance of optical coherence tomography (SD-OCT) in managing pediatric optic pathway gliomas (OPGs) in children younger than 5 years of age. A retrospective monocentric study was conducted. SD-OCT scans were obtained using the handheld iVue system to assess peripapillary retinal nerve fibre layer (pRNFL) thickness at three time points: baseline (OCT1), end of treatment (OCT2), and at last follow-up (OCT3). We compared the median value of pRNFL (and interquartile range-IQR) at different follow-up times and in different sub-groups (stable disease-SD, partial response-PR, and progression disease-PD). Thirteen children younger than 5 years of age were included. The Median follow-up time was 3.9 years (IQR 1.2). Six patients showed a pRNFL change of more than 10% during follow-up. Seven patients showed PD during follow-up. Median pRNFL at baseline was 81.5 µm (IQR 31.5); median pRNFL at the end of treatment was 73 µm (IQR 33); median pRNFL at last follow-up was 72 µm (IQR 38.5). The mean pRNFL at baseline was significantly lower than the mean normative values. Only subjects with PD showed pRNFL change close to statistical significance. This study confirms the role of SD-OCT in managing OPGs for therapeutic decisions and strategy planning of visual rehabilitation.